Filler Dispersion and Unidirectional Sliding Characteristics of As-Cast and Multi-Pass Friction Stir Processed ZrB2/AA7075 In-Situ Composites - Prasad R.; Kumar H.; Kumar P.; Tewari S.P.; Singh J.K. (My University, 2025)
Despite the fabrication of particulate-reinforced composites via friction stir processing (FSP), an attempt was made to utilize FSP for the homogenization of filler dispersion in ZrB2/AA7075 in-situ composites fabricated via stir casting route, with varying weight percentages of ZrB2. The friction stir processing was performed for up to three passes with 100% overlap. The as-cast and friction stir processed (FSPed) composites were characterized for their microstructural, microhardness, and tribological behavior. The microstructural features revealed the increase in the misorientation angle among grain boundaries, with an increase in ZrB2 content and a number of FSP passes. Furthermore, the homogeneity of ZrB2 particles in the Al alloy matrix was significantly influenced by the number of FSP passes, which was quantified by Lorenz curves and Gini Indices. The FSPed alloy and composites exhibited higher microhardness as compared to their un-processed counterparts. The tribological behavior was investigated for three different load levels, i.e., 15 N, 30 N, and 45 N. The slope of the wear-rate at 45 N revealed that the Al-alloy exhibited a considerable increase in wear severity, whereas as-cast and FSPed composites did not show a significant increase. Both wear-rate and coefficient of friction decreased with an increase in the number of FSP passes and ZrB2 content. The scanning electron micrographs of worn surfaces confirmed the reduction in adhesion, abrasion, and delamination with the number of FSP passes. However, the synergism among the three depicted the overall tribological behavior. © 2020 Royal Society of Chemistry. All rights reserved.